![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
2个回答
展开全部
用Taylor 展开至x^4:e^sinx ~ 1+x+x^2/2 - x^4/8
原极限 = lim{x->0} [(e^x-1) - (e^x-1)^3/3! - (e^sinx - 1)]/(81x^4)
= lim{x->0} [(e^x - (x+x^2/2!+x^3/3!)^3/3! - e^sinx]/(81x^4)
= lim{x->0} [x^4/4! + x^4/8 - x^4/4 ]/(81x^4)
= -1/972
原极限 = lim{x->0} [(e^x-1) - (e^x-1)^3/3! - (e^sinx - 1)]/(81x^4)
= lim{x->0} [(e^x - (x+x^2/2!+x^3/3!)^3/3! - e^sinx]/(81x^4)
= lim{x->0} [x^4/4! + x^4/8 - x^4/4 ]/(81x^4)
= -1/972
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询